Navigation and Waterpower : Adaptation and Technology on Canadian Canals - Desjardins, Pauline (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Navigation; Énergie hydraulique

The Application of Steam Navigation to the St. Lawrence 1809-1840 - Wilson, George H. (Université McGill, 1961)
Keywords: Navigation; Énergie hydraulique

Montréal et les débuts de la navigation à vapeur sur le St-Laurent - Dubuc, Alfred (Revue d'histoire économique et sociale, 1967)
Keywords: Molson (famille); Navigation

La navigation à vapeur sur le Saint-Laurent - Baker, Victoria A. (De la voile à la vapeur: la construction de navires dans les environs de Québec et de Montréal / From Sail to Steam (...), 1982)
Keywords: Navigation; Port; Voie maritime

Montréal et les débuts de la navigation à vapeur sur le Saint-Laurent - Dubuc, Alfred (La grande mouvance, 1990)
Keywords: Molson (famille); Navigation; Voie maritime

Steamboat connections : Montreal to Upper Canada, 1816-1843 - Mackey, Frank (McGill-Queen's University Press, 2000)
"In Steamboat Connections Frank Mackey gives us a narrative account of the first twenty-five years of steam navigation along the St. Lawrence and Ottawa Rivers. Relying on a wealth of primary archival sources, Mackey focuses on the development of steamer traffic from 1816 - when the foundations were laid for the first stage and steamboat line between Montreal and Upper Canada - to the early 1840s - when locks, canals, innovations, and human daring conquered the rapids on those rivers and allowed for navigation between Montreal and the Great Lakes. He shows how, starting in 1841, small steamers ran "the circuit" - down the rapids of the St. Lawrence to Montreal and then back up to Kingston and other Great Lakes ports via the Ottawa River and the Rideau Canal." "Mackey introduces the entrepreneurs who forged this important link between Montreal and the nation's interior and chronicles the course of their industry, correcting previous misinterpretations. He sheds light not only on steamboats but also on the social, commercial, and geographical development they made possible. He shows that the history of this country, a land with vast expanses and a harsh climate, cannot be fully appreciated without looking at the different modes of transportation that made it possible."--BOOK JACKET.
Keywords: Navigation

The St. Lawrence Ship Channel, 1805-1865 - Corley, Nora T. (Cahiers de géographie du Québec, 1967)
Keywords: Navigation

The Montreal Ship Channel, 1805-1865 - Corley, Nora (Université McGill, 1961)
Keywords: Navigation

“The Severity of This Service…” Canadien Inland Mariners in the Early Post-Conquest Era, 1760 to 1817 - More, John David (Université Queen's, 2021)
Keywords: Guerre; Navigation

De la voile à la vapeur: la construction des navires dans les environs de Québec et de Montréal / From Sail to Steam (...) - Baker, Victoria A.; Dutton, Diana (Musée Marsil de Saint-Lambert / Marsil Museum of Saint-Lambert, 1982)
Keywords: Construction navale; Navigation

Le Saint-Laurent. Grande porte de l'Amérique - Lasserre, Jean-Claude (Hurtubise HMH, 1980)
Keywords: Navigation; Voie maritime

The Lachine Canal - Cureton, Edward A. (Université McGill, 1957)
Keywords: Lachine (canal); Navigation

The Construction of the First Lachine Canal, 1815-1826 - Tulchinsky, Gerald (Université McGill, 1960)
Keywords: Lachine (canal); Navigation

Le Saint-Laurent, comme une rue principale - Franck, Alain (Continuité, 2001)
Keywords: Navigation; Voie maritime

Les chantiers navals du canal Lachine - Corbel, Nadine H. J. (Université Concordia, 1991)
Keywords: Construction navale; Navigation

Canada's Bid for the Traffic of the Middle West: A Quarter Century of the History of the St. Lawrence Waterway, 1849-1874 - Mckee, Samuel Jr. (Report of the Annual Meeting of the Canadian Historical Association / Rapports annuels de la Société historique du Canada, 1940)
Keywords: Navigation; Voie maritime

Au canal de Lachine - Desjardins, Pauline (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Lachine (canal); Navigation

La rivière des Prairies - Dupont, Antonin (Il était une fois... Montréal-Nord, 2002)
Keywords: Navigation; Rivière des Prairies

Une artère vitale: le fleuve - Gelly, Alain (Cap-aux-Diamants, 2012)
Keywords: Chemins de fer; Navigation; Routes

John Richardson et la construction du canal de Lachine - Laliberté, Pierre (Cahier de la Société historique de Montréal, 1983)
Keywords: Lachine (canal); Navigation; Richardson, John

En rade: marins à Montréal (1851-1896) - Bélisle-Desmeules, David (Domaine histoire, 2019)
Keywords: Navigation; Port; Travail; Vieux-port

" Du chemin qui marche " au chemin du Roy à la Pointe-aux-Trembles - Desjardins, Pierre (Histoire Québec, 2010)
Keywords: Navigation; Pointe-aux-Trembles; Routes; Voirie

Ravenscrag: the Allan Royal Mail Line - Appleton, Thomas E. (McClelland and Stewart, 1974)
Keywords: Allan Royal Mail Line; Allan, Andrew; Allan, Hugh; Navigation

La compagnie maritime Allan: de l'Écosse au Canada au XIXe siècle - Blondel-Loisel, Annie (Là-bas, 2009)
Keywords: Allan Royal Mail Line; Allan, Andrew; Allan, Hugh; Navigation

Voies pointelières d'hier et d'aujourd'hui - Desjardins, Pierre (Atelier d'histoire de Pointe-aux-Trembles, 2006)
Keywords: Chemins de fer; Navigation; Pointe-aux-Trembles; Quartiers

Studies of Businessmen in the Development of Transportation and Industry in Montreal, 1837-1853 - Tulchinsky, Gerald (Université de Toronto, 1971)
Keywords: Bourgeoisie; Chemins de fer; Hommes d'affaires; Marchands; Navigation

The River Barons. Montreal Businessmen and the Growth of Industry and Transportation 1837-1853 - Tulchinsky, Gerald (University of Toronto Press, 1977)
Keywords: Bourgeoisie; Chemins de fer; Hommes d'affaires; Marchands; Navigation